The Efficacy of Type F Fly Ash from Paiton Power Plant on the Compressive Strength of Concrete - Wahyudi, Thesalonika Octaviana; Kartini, Wahyu; Puspitasari, Nia Dwi (UKaRsT, 2025)
Portland cement is the primary binder in concrete and plays a crucial role in defining its structural performance. However, its production contributes approximately 7% of global carbon dioxide emissions, necessitating sustainable alternative materials. One potential material is Type F fly ash derived from coal combustion waste in steam power plants. This study aims to evaluate the effectiveness of Type F fly ash from the Paiton Power Plant as a sustainable cement replacement material in concrete based on compressive strength performance. Fly ash was activated using an alkaline solution consisting of NaOH and Na₂SiO₃ with a ratio of 1:2.5, where the NaOH concentration was maintained at 10 M. Two water–cement ratios (W/C) of 0.45 and 0.55 were employed to investigate their influence on workability and compressive strength. Cylindrical specimens were tested at 28 days with fly ash replacement levels of 0%, 80%, 90%, and 100% by weight of cement. The results indicate that increasing fly ash content significantly enhances compressive strength. The optimal performance was achieved with 100% fly ash replacement, yielding a compressive strength of 48.48 MPa or an increase of 102.4% compared to conventional concrete. This performance is attributed to the high silica content of Type F fly ash, which promotes the formation of dense N-A-S-H gel through alkaline activation, resulting in a more compact and less porous microstructure. These findings demonstrate that Type F fly ash from the Paiton Power Plant can effectively function as a primary binder, offering a sustainable alternative for high-performance concrete production.